PERKEMBANGAN PEMBINAAN KOMUNITAS PECINTA ALAM UNTUK OLAHRAGA PANJAT TEBING DI KABUPATEN BONE - Darul Husnul (Program Studi Ilmu Keolahragaan, 2023)
This study aims to determine the development of rock climbing in the nature lovers community in Bone Regency. This research uses descriptive qualitative research, the subject of this research is the entire chairman of the nature lovers community in Bone district consisting of 16 chairmen. The object of this research is about the development of rock climbing sports in the Bone district nature lovers community. With data collection techniques observation, questionnaires and documentation. This research was conducted in all student organizations of nature lovers in Bengkulu Province. Based on the results of the study, it can be seen that the results of the development of rock climbing sports coaching in the Bone district nature lovers community with human resources with a percentage of 63.96% are categorized as good, facilities and infrastructure with a percentage of 66.56% are categorized as good, training programs with a percentage of 78.75% are categorized as good, and achievements with a percentage of 65.83% are categorized as good. with an average of 68.77% in the good category so it can be concluded that the development of rock climbing sports coaching for nature lovers students in Bone district is in the good category.